2022
DOI: 10.3390/ijms23052730
|View full text |Cite
|
Sign up to set email alerts
|

C2H2 Zinc Finger Proteins Response to Abiotic Stress in Plants

Abstract: Abiotic stresses have already exhibited the negative effects on crop growth and development, thereby influencing crop quality and yield. Therefore, plants have developed regulatory mechanisms to adopt against such harsh changing environmental conditions. Recent studies have shown that zinc finger protein transcription factors play a crucial role in plant growth and development as well as in stress response. C2H2 zinc finger proteins are one of the best-studied types and have been shown to play diverse roles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 97 publications
(279 reference statements)
1
38
0
Order By: Relevance
“…Di19 protein is a type of zinc finger protein, which belongs to Cys2/His2 (C2H2) zinc-finger protein. Zinc finger protein has strong function and has outstanding performance in coping with abiotic stress [ 42 ]. The first Di19 protein was found in Arabidopsis thaliana [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Di19 protein is a type of zinc finger protein, which belongs to Cys2/His2 (C2H2) zinc-finger protein. Zinc finger protein has strong function and has outstanding performance in coping with abiotic stress [ 42 ]. The first Di19 protein was found in Arabidopsis thaliana [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…C2H2 zinc finger proteins have been shown to participate as a pivotal regulator of Reactive Oxygen Species (ROS) signaling in the signal transduction of water stress [14], and oxidative stress, in rice [15]. It has been demonstrated previously that repressing the expression of zinc finger proteins under drought stress was linked to enhancing tolerance to drought stress through a complex regulatory network in plants [16]. This suggests that Nipponbare plants sensed the severe drought condition as stress and responded to it by decreasing the abundance of C2H2-type domain-containing protein.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of a gene is often used to predict its function. Previous findings have shown that the expression of C2H2-ZFP genes was affected by tissue differences and various abiotic stresses [ 46 , 53 ]. Our results showed that among the selected SbC2H2-ZFPs, most genes were expressed in roots higher than those in leaves or stems, but almost all SbC2H2-ZFP members were expressed in roots, stems, and leaves.…”
Section: Discussionmentioning
confidence: 99%